Tenofovir disoproxil fumarate in Asian or Pacific Islander chronic hepatitis B patients with high viral load (≥ 9 log10 copies/ml). (28th October 2014) - Fung, Scott; Gordon, Stuart C.; Krastev, Zahary; Horban, Andrzej; Petersen, Jörg; Sperl, Jan; Gane, Edward; Jacobson, Ira M.; Yee, Leland J.; Dinh, Phillip; Martins, Eduardo B.; Flaherty, John F.; et al.
Abstract Background & Aims We evaluated the antiviral response of Asian or Pacific Islander (API) patients with chronic hepatitis B (CHB) who had baseline high viral load (HVL), defined as pre‐treatment hepatitis B virus (HBV) DNA ≥9 log10 copies/ml, following up to 288 weeks of tenofovir disoproxil fumarate (TDF) treatment. Methods A total of 205 HBeAg‐negative and HBeAg‐positive self‐described API patients received 48 weeks of TDF 300 mg (HVL n = 18) or adefovir dipivoxil 10 mg (HVL n = 15) in a blinded fashion, followed by open‐label TDF for an additional 240 weeks. The proportions of HVL vs. non‐HVL patients with HBV DNA <400 copies/ml were compared. Mean declines in HBV DNA were evaluated in API vs. non‐API patients. Results Throughout the first 72 weeks of treatment, a smaller proportion of HVL API patients reached HBV DNA <400 copies/ml than non‐HVL API patients. However, after this timepoint similar proportions of HVL and non‐HVL API patients achieved HBV DNA <400 copies/ml (100% vs. 97%, respectively), which was maintained through week 288, where 92% of HVL patients and 99% of non‐HVL API patients on treatment had HBV DNA <400 copies/ml. During the 288 weeks of treatment, API patients had similar mean HBV DNA declines as non‐API patients, regardless of whether patients were HVL or non‐HVL. No API HVL patient had persistent viremia at week 288. No resistance was detected among HVL or non‐HVL patients. Conclusions API patients with HVL CHB achieve HBV DNA <400 copies/ml with long‐term TDF treatment; however, achieving viral suppression may take longer for HVL patients relative to non‐HVL API patients.